PENGARUH FLEKSIBILITAS KERJA TERHADAP KEPUASAN KERJA DENGAN WORK-LIFE BALANCE SEBAGAI PEMEDIASI - R Nona Oktarina; Adi Rahmat; Agus Seswandi (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
In the context of government organizations, job satisfaction for employees has different characteristics compared to the private sector. Factors such as work flexibility and work life balance are important to pay attention to because employees in this sector often face high work demands and irregular schedules. The aim of this research is to determine the effect of work flexibility on job satisfaction with work-life balance as a mediator. This research is a type of quantitative research with a causality research design and the population is ASN and honorary staff at the Indragiri Hilir Regency DPRD Secretariat Office with a population of 420 people. Data collection techniques using questionnaires and distribution using Google Form. The data analysis tool in this research is Structural Equation Modeling (SEM) processed using SmartPLS 3.2.9 for data processing. The results of this research are that work flexibility has a positive influence on employee job satisfaction at the Indragiri Hilir Regency DPRD office, both directly and indirectly through the mediation of work-life balance.